New perspectives on active pediculosis detection in schoolchildren from Southern Brazil (Research, Society and Development, 2021)
The present study aims to analyze the prevalence and risk factors of active pediculosis and to compare the efficacy and sensitivity of the vacuum method with the comb method and the visual inspection with a magnifying glass in order to determine the best methodology to detect active pediculosis among schoolchildren from Paraná state. Each child was examined by the three methods in sequence and a playful activity was introduced to increase the children likelihood to participate in the study. Additionally, hair characteristics and other risk factors as sex, age, and area of living were take into consideration to measure epidemiological aspects. From a total of 358 schoolchildren from southern Brazil, overall pediculosis prevalence was 45.5%, while active pediculosis prevalence was 13.1%. Regarding active pediculosis, there was no statistical difference among sex. However, nine-year-old girls were most likely to have active pediculosis. The vacuum method was 5.96 and 11.29 times more efficacious than the magnifying glass method and the comb method, respectively, and also had higher sensitivity (74.5%) in detecting active pediculosis. When analyzing hair characteristics, children with long and wavy/curly hair were more often diagnosed by the vacuum method than children with short and wavy/curly hair. The vacuum method was the most effective method and proved to be an optimal option to detect active pediculosis among schoolchildren, mostly in children with wavy/curly hair.